The effects of rehydration of cement in recycled crushed concrete road base - Deilami, Sahar; Leek, C.; Nikraz, Hamid; Asadi, H. (2015)
© 2015 Taylor & Francis Group, London.There has been a trend towards the increasing use of Recycled Crushed Concrete (RCC) as a road base inWestern Australia to reduce the consumption of new virgin materials. However, it has been observed that in some cases the recycled road base has developed very high stiffness and in some cases exhibited reflective cracking in the asphalt surface. It is postulated that this high stiffness and shrinkage results from rehydration of cement in the road base. Hence, research has been undertaken to investigate methods to control shrinkage cracking of RCC, and RCC blended with two recycled aggregate types, namely, brick & tile and ferricrete, for road base, whilst retaining the inherent strength of the base material. The strength tests on the various blends showed that with the addition of brick & tile or ferricrete to RCC, the resulting materials remained “stiff”. Thus, recycled materials are good material for heavy duty pavements.